A new machine learning approach for predicting the response to anemia treatment in a large cohort of End Stage Renal Disease patients undergoing dialysis. (1st June 2015) - Barbieri, Carlo; Mari, Flavio; Stopper, Andrea; Gatti, Emanuele; Escandell-Montero, Pablo; Martínez-Martínez, José M.; Martín-Guerrero, José D.
Abstract: Chronic Kidney Disease (CKD) anemia is one of the main common comorbidities in patients undergoing End Stage Renal Disease (ESRD). Iron supplement and especially Erythropoiesis Stimulating Agents (ESA) have become the treatment of choice for that anemia. However, it is very complicated to find an adequate treatment for every patient in each particular situation since dosage guidelines are based on average behaviors, and thus, they do not take into account the particular response to those drugs by different patients, although that response may vary enormously from one patient to another and even for the same patient in different stages of the anemia. This work proposes an advance with respect to previous works that have faced this problem using different methodologies (Machine Learning (ML), among others), since the diversity of the CKD population has been explicitly taken into account in order to produce a general and reliable model for the prediction of ESA/Iron therapy response. Furthermore, the ML model makes use of both human physiology and drug pharmacology to produce a model that outperforms previous approaches, yielding Mean Absolute Errors (MAE) of the Hemoglobin (Hb) prediction around or lower than 0.6 g/dl in the three countries analyzed in the study, namely, Spain, Italy and Portugal. Abstract : Highlights: Prediction algorithm trained and tested on a large sample of real clinical data. Prediction improvement based on red blood cell dynamics and drug kinetics. There is still room for improvement of anemia management in dialysis. The model presented is suitable for the application in a daily clinical practice.